Haro Hara Song: History of Protest Music in Aceh 2000-2003 - Rika Wirandi; Rico Gusmanto; Dwindy Putri Cufara; Susandro Susandro; Hatmi Negria Taruan (Universitas Negeri Medan, 2026)
The song Haro Hara is one of the protest songs whose lyrics contain four bloody events during the 1998 conflict or after the revocation of the Military Operations Area (DOM) status in Aceh. This study aims to examine the development, social and political influences, and the phases of the ban on the protest song Haro Hara during the armed social conflict in Aceh. This study uses a qualitative approach based on archives, employing netnography techniques that emphasize the search for online data, archives, and interviews. The primary data sources are musical artifacts in the form of physical cassette tape releases of the Nyawöung album and several related Acehnese music albums, as well as digital files of related songs on YouTube, Instagram, Facebook, and TikTok. This study found that the song Haro Hara is considered a product of journalism in the form of music that tells and records four conflict events that claimed civilian casualties in Aceh. The song is considered to contain propaganda and is included in the list of “banned songs” that were once censored along with other Acehnese songs with protest and political nuances. The song Haro Hara was removed from the second album released by Nyawöung in 2004 because it was considered by the Regional Military Emergency Authority (PDM) of Nanggroe Aceh Darussalam (NAD) to be provocative and to stir up the spirit of resistance among the Acehnese people who wanted independence and were considered to be siding with the Free Aceh Movement (GAM). Furthermore, the musical concepts championed by the Nyawöung band—including in the song Haro Hara—have had a significant impact on the dynamics of music and local politics in Aceh during the conflict and up to the present day.